Automating dynamic layout construction - Zouein, P.P. (2017)
A critical problem in dynamic environments and especially on construction sites is coordinating the use of limited space to accommodate resources and their changing demand for space over time. This paper presents a heuristic model that allocates site space to resources associated with an activity schedule so that no spatial conflicts would arise and all resources can be functional. It addresses the dynamic layout planning problem, which involves creating a sequence of layouts that span the duration of construction of a project, given the schedule with activity resources and the timing of their presence on site. The MoveSchedule model, presented here, characterizes changing resource space needs over time and uses a heuristic procedure to automatically construct a dynamic layout while allowing space reuse.